2006
DOI: 10.1097/01.meg.0000230094.21911.f8
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal capsule endoscopy in patients refusing conventional endoscopy for the study of suspected esophageal pathology

Abstract: Esophageal capsule endoscopy is an adequate alternative diagnostic method for the study of gastroesophageal reflux disease and for the screening of esophageal varices in patients refusing to undergo conventional upper gastrointestinal endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
3
17
0
2
Order By: Relevance
“…Results of a survey of practicing gastroenterologists suggested an even lower screening rate of 39% [23] . Alternative methods to EGD have been studied for variceal screening, including transnasal endoluminal ultrasound [24] , platelet count/spleen diameter ratio [25] , multidetector computed tomography esophagography [26] , and esophageal capsule endoscopy [10,11,27] . To date, no method has proven accurate enough to replace EGD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of a survey of practicing gastroenterologists suggested an even lower screening rate of 39% [23] . Alternative methods to EGD have been studied for variceal screening, including transnasal endoluminal ultrasound [24] , platelet count/spleen diameter ratio [25] , multidetector computed tomography esophagography [26] , and esophageal capsule endoscopy [10,11,27] . To date, no method has proven accurate enough to replace EGD.…”
Section: Discussionmentioning
confidence: 99%
“…There has been some concern about the mixed results of capsule endoscopy use for evaluation of esophageal pathology, such as varices, Barrett's esophagus, or esophagitis [27][28][29] . It is thought that the mixed results of capsule endoscopy may have to do with deviations from the standard ingestion procedure recommended by the manufacturer [30] .…”
Section: Discussionmentioning
confidence: 99%
“…The overall results were relatively poor, meaning that OCE is unlikely to replace OGD in non-specific indications or in those who refuse OGD, as proposed by some authors 47. However, these data have been criticised because of the relatively small size of this trial with regard to the number of indications and because the STARD recommendation of an intention-to-diagnose analysis was not followed.…”
Section: Oesophageal Capsule Endoscopymentioning
confidence: 90%
“…Several reports have indicated that ECE can provide clear images of esophageal diseases, including Barrett's esophagus and esophagitis [1114], and that it is useful for detecting EV [5, 13, 15]. However, few such reports have been generated from Asian countries, including Japan.…”
Section: Introductionmentioning
confidence: 99%